Architecting Scalable Cloud Systems: Advanced API Integration Strategies and Best Practices - Himaja Sabbineni, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the evolution and implementation of scalable cloud architectures with advanced API integration strategies in modern enterprise environments. The article explores fundamental aspects of distributed computing, container orchestration, and high-availability patterns while examining their impact on system performance and business outcomes. Through an analysis of current industry practices, the article demonstrates how organizations leverage various API protocols, performance optimization techniques, and security measures to build resilient cloud infrastructures. The article further delves into real-world applications across e-commerce, financial services, logistics, and media streaming platforms, highlighting transformative improvements in operational efficiency and user experience. By examining implementation best practices, including architecture design patterns, security considerations, monitoring strategies, and DevOps integration, the research provides valuable insights for organizations pursuing cloud transformation initiatives. The article also explores emerging trends in serverless computing, edge computing, and artificial intelligence, offering a forward-looking perspective on the evolution of cloud architectures and their role in driving business innovation.
Keywords: Cloud Architecture; API Integration; Distributed Computing; Scalability; DevOps Automation